GE_GERICHTE C/4066/2017 vom 14. Mai 2018 - GE Cour de justice (2018)
TRANSACTION COUPLÉE ; ACTION EN CONTESTATION ; LOYER INITIAL ; FORMULE OFFICIELLE ; ABUS DE DROIT ; NULLITÉ ; CRAINTE FONDÉE ; HONORAIRES ; AVOCAT | CO.254; CO.270; OBLF.19